2008
DOI: 10.1099/ijs.0.65377-0
|View full text |Cite
|
Sign up to set email alerts
|

Geobacter uraniireducens sp. nov., isolated from subsurface sediment undergoing uranium bioremediation

Abstract: A Gram-negative, rod-shaped, motile bacterium, strain Rf4 T , which conserves energy from dissimilatory Fe(III) reduction concomitant with acetate oxidation, was isolated from subsurface sediment undergoing uranium bioremediation. The 16S rRNA gene sequence of strain Rf4 T matched sequences recovered in 16S rRNA gene clone libraries constructed from DNA extracted from groundwater sampled at the same time as the source sediment. Cells of strain Rf4 T were regular, motile rods, 1.2-2.0 mm long and 0.5-0.6 mm in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
78
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 23 publications
0
78
0
2
Order By: Relevance
“…Comparison of the G. uraniireducens transcriptome in cells grown in sediments vs defined medium Geobacter uraniireducens was studied, because it was isolated from the uranium-contaminated site in Rifle, Colorado, and its 16S rRNA gene sequence matched one of the sequences that predominated during in situ uranium bioremediation (Shelobolina et al, 2008). Microarray comparisons between G. uraniireducens cells grown in sediments vs the soluble electron acceptor, fumarate, showed that 1964 genes (1084 upregulated, 882 downregulated) had at least a twofold difference in transcript levels (Table 2; Supplementary Tables S1 and S2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Comparison of the G. uraniireducens transcriptome in cells grown in sediments vs defined medium Geobacter uraniireducens was studied, because it was isolated from the uranium-contaminated site in Rifle, Colorado, and its 16S rRNA gene sequence matched one of the sequences that predominated during in situ uranium bioremediation (Shelobolina et al, 2008). Microarray comparisons between G. uraniireducens cells grown in sediments vs the soluble electron acceptor, fumarate, showed that 1964 genes (1084 upregulated, 882 downregulated) had at least a twofold difference in transcript levels (Table 2; Supplementary Tables S1 and S2).…”
Section: Resultsmentioning
confidence: 99%
“…Contrary to the often-repeated statement that the most environmentally relevant microorganisms cannot be studied in pure culture, it has become increasingly apparent that pure cultures of some of the most environmentally relevant organisms can be recovered (Chisholm et al, 1992;Button et al, 1993;Rappe et al, 2002;Konneke et al, 2005;Nevin et al, 2005;Giovannoni and Stingl, 2007;Shelobolina et al, 2008;Holmes et al, 2008a). When these organisms are available in pure culture, it is possible to combine genome sequence information with physiological, transcriptomic and proteomic studies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both the site and the field bioremediation research have been described extensively elsewhere [5][6][7] and a more complete description of the ongoing work at the Old Rifle UMTRA site may be found at http://www.pnl.gov/nabir-umtra/intro.stm. In the summer of 2008, much of the research activity was focused upon the collection of samples for proteomic analyses [5,[8][9][10][11], and timely information about the extent of uranium immobilization or remobilization in groundwater samples was useful to the research team in the timing of sample collection.…”
Section: Introductionmentioning
confidence: 99%